Severe Gingival Enlargement with Coexisting Erosive Lichen Planus in Severe Chronic Periodontitis Patient. (9th March 2015) - Sharma, Ambika; Aggarwal, Chakshu; Mathur, Vijay P.; Sardana, Divesh
Abstract : Plaque induced gingival enlargement is most commonly seen and when encountered simultaneously with erosive lichen planus poses a challenge to the treating dentist. Prognosis of one condition may influence the prognosis of another condition. The presented case highlights the significance of proper diagnosis and the management of simultaneously occurring gingival lesions. A 49-year-old hypertensive female presented with painful enlarged bleeding and suppurating gums with burning sensation on eating food along with long-term usage of antihypertensive drug amlodipine known for its gingival enlargement effect. All these multiple factors led to diagnostic dilemma. Effective management of the gingival enlargement was done by using electrocautery to rehabilitate the functions and esthetics of the patient. Gingival condition was also complicated by the presence of coexisting lichen planus which was predominantly erosive for which topical corticosteroid, antifungal, and antimicrobial agents were prescribed. Eight-month follow-up did not show recurrence of gingival enlargement. Electrocautery is an effective tool for the gingivectomy in severe inflammatory type of gingival enlargement because of rapid postoperative hemostasis. For the management of erosive lichen planus, long-term use of topical corticosteroids is an effective approach. Maintenance of oral hygiene and regular follow-ups are essential for these conditions.